2022
DOI: 10.1007/s00787-022-01972-1
|View full text |Cite
|
Sign up to set email alerts
|

The added value of a micro-level ecological approach when mapping self-regulatory control processes and externalizing symptoms during adolescence: a systematic review

Abstract: Deficits in self-regulatory control (SRC) represent a core characteristic of externalizing (EXT) symptoms (e.g., rule-breaking behavior or aggressive behaviors) in adolescents. This review aims to specify the added value of ecologically valid assessments at a micro-level when examining the associations between SRC and EXT symptoms in adolescents. This systematic review was reported according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. The search strategy addressed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…An important future direction includes the examination of trait versus state impulsivity. Recent advances in technology (e.g., smart phones and wearables) and intensive longitudinal statistical approaches have produced a flurry of studies testing the dynamics or fluctuations of emotional and behavioral problems at micro timescales ; for a review, see Urben et al, 2022). Some research has also identified state-like fluctuations in other neurodevelopmental traits that were considered relatively stable (i.e., callous-unemotional traits; .…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%
“…An important future direction includes the examination of trait versus state impulsivity. Recent advances in technology (e.g., smart phones and wearables) and intensive longitudinal statistical approaches have produced a flurry of studies testing the dynamics or fluctuations of emotional and behavioral problems at micro timescales ; for a review, see Urben et al, 2022). Some research has also identified state-like fluctuations in other neurodevelopmental traits that were considered relatively stable (i.e., callous-unemotional traits; .…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%
“…ACEs have been associated with structural and functional impacts on the developing brain, leading to significant difficulties in self-regulatory functioning (Bellis et al, 2014). Poor self-regulatory control can predispose an individual to engage in a wide range of risky behaviours that may bring them to the attention of community police officers, including premature sexual activity, alcohol/substance misuse, suicide attempts and intimate partner violence (McManus et al, 2022;Stinson et al, 2023;Urben et al, 2022). A worldwide meta-analysis of 119 longitudinal studies found that ACEs could predict aggressive, criminal and violent behaviour in later life (Derzon, 2010), while a more recent systematic review of meta-analyses found that childhood adversity, particularly family-related trauma, consistently predicted both offending and persistence in criminal behaviour across the lifespan (Basto-Pereira & Farrington, 2022).…”
Section: Adverse Childhood Experiences (Aces)mentioning
confidence: 99%